2022
DOI: 10.3389/fpls.2022.855486
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome and Small RNA Sequencing Reveal the Mechanisms Regulating Harvest Index in Brassica napus

Abstract: Harvest index (HI), the ratio of harvested seed weight to total aboveground biomass weight, is an economically critical value reflecting the convergence of complex agronomic traits. HI values in rapeseed (Brassica napus) remain much lower than in other major crops, and the underlying regulatory network is largely unknown. In this study, we performed mRNA and small RNA sequencing to reveal the mechanisms shaping HI in B. napus during the seed-filling stage. A total of 8,410 differentially expressed genes (DEGs)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 120 publications
0
2
0
Order By: Relevance
“…Therefore, while improving the photosynthetic efficiency, it is also important to improve the transport and distribution capacity of photoassimilates. Collaboration of “source-flow-sink” as the main factor affecting photosynthate allocation, sufficient source, smooth flow, and large storage capacity is the ideal breeding target and helps to maximize the transport and distribution capacity of photosynthates to balance source–sink dynamics [ 46 ]. Numerous studies on source and sink systems have been conducted that can be seen when we search for critical information, but less progress has been made in crops’ understanding of flow and the vascular bundles (mostly the phloem) systems.…”
Section: Advances In Vascular Bundle and “Source-flow-sink” Allocationmentioning
confidence: 99%
“…Therefore, while improving the photosynthetic efficiency, it is also important to improve the transport and distribution capacity of photoassimilates. Collaboration of “source-flow-sink” as the main factor affecting photosynthate allocation, sufficient source, smooth flow, and large storage capacity is the ideal breeding target and helps to maximize the transport and distribution capacity of photosynthates to balance source–sink dynamics [ 46 ]. Numerous studies on source and sink systems have been conducted that can be seen when we search for critical information, but less progress has been made in crops’ understanding of flow and the vascular bundles (mostly the phloem) systems.…”
Section: Advances In Vascular Bundle and “Source-flow-sink” Allocationmentioning
confidence: 99%
“…By sequencing high-and low-oil-content rapeseed seeds, 302 differentially expressed miRNAs were identified, and further analysis through degradation sequencing and bioinformatics revealed that nine target genes may be involved in seed oil synthesis [19]. Analysis of the transcriptomes of different rapeseed varieties with varying harvest indices revealed that miRNAs are associated with the rapeseed harvest index, with bna-miR396 potentially controlling seed development and enhancing the harvest index [20]. In addition to rapeseed, miRNAs involved in oil and lipid biosynthesis have been identified in other oil crops as well.…”
Section: Introductionmentioning
confidence: 99%